Tracking actions to address malnutrition in all its forms - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
To hold governments and other national stakeholders accountable for their actions to improve nutrition, it is critical to track their progress in implementing interventions, programs, and policies. This chapter reviews the degree to which these stakeholders have implemented actions to reduce malnutrition in all its forms. It also reviews some of the tools available to track implementation.